Clinical characteristics and chest x-ray and computed tomography findings in different clinical severity grading of COVID-19 patients - Gurung, Sailesh; Adhikari, Shital; Bhattarai, Madhur Dev; Gauli, Basanta; Adhikari, Deepak; Poudel, Bigyan; Puri, Niraj; Wagley, Pratik; Patel, Sunil (Journal of Chitwan Medical College, 2021)
Background: Clinical assessment, chest X-ray (CXR) and high-resolution computed tomography (HRCT) are used in the Corona virus disease-19 (COVID-19) management. The aim of the study was to determine the clinical characteristics and CXR and HRCT findings in COVID-19 patients with different clinical severity. Methods: This was a hospital-based cross-sectional study conducted at Chitwan Medical College, Department of Pulmonary and Critical Care Medicine from September to December 2020. Data from sixty adult patients with moderate (non-severe), severe, and critical COVID 19 disease having both CXR and HRCT were collected and were analyzed using SPSS version 16. Results: Median age of patients in our hospital-based study was 59.9 years and 76.7% were male, 30% had diabetes, and 35% had hypertension. Respiratory rate (p=0.001) and shortness of breath (p= 0.011) significantly increased and oxygen saturation (SpO2) (p<0.001) decreased with increase in clinical severity of COVID-19 disease. Among the moderate, severe and critical clinical severity groups, there was significant difference in the HRCT findings like ground-glass opacity (GGO), consolidation, septal thickening, crazy paving pattern, bronchiectasis and fibrosis (p<0.05). GGO was the most common finding. Bilateral consolidation in CXR and multiple lobes in both lungs involvement in HRCT were similar across the moderate, severe and critical clinical severity (p>0.05). Conclusions: There was no difference in CXR and HRCT findings across moderate, severe and critical clinical severities of COVID-19; future study performing CXR whenever HRCT is done for any indication may similarly indicate the situation in mild COVID-19 disease.